2019
DOI: 10.3390/molecules24152832
|View full text |Cite
|
Sign up to set email alerts
|

MMI-0100 Ameliorates Dextran Sulfate Sodium-Induced Colitis in Mice through Targeting MK2 Pathway

Abstract: Backgrounds: This study aimed to investigate the protective effects of MMI-0100, a cell-penetrating peptide inhibitor of MAPK-activated protein kinase II (MK2), on acute colitis induced by dextran sodium sulfate (DSS). Mice were injected intraperitoneally with different doses of MMI-0100 (0.5 and 1 mg/kg per day, six days). The physiological indexes, the parameters for colonic pathological injury and the intensity of inflammatory responses were evaluated by histological staining, quantitative PCR, western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In our present work, we further identified the abilities of mangiferin on attenuating cardiac oxidative stress, inflammation and fibrosis via inhibiting the activation of TGF-β1/p38/MK2 signaling pathway. MMI-0100 is a cell-penetrating peptide inhibitor of MK2 [ 34 ]. MMI-0100 had exerted anti-cardiac fibrosis ability [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our present work, we further identified the abilities of mangiferin on attenuating cardiac oxidative stress, inflammation and fibrosis via inhibiting the activation of TGF-β1/p38/MK2 signaling pathway. MMI-0100 is a cell-penetrating peptide inhibitor of MK2 [ 34 ]. MMI-0100 had exerted anti-cardiac fibrosis ability [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress also could activate p38 MAPK, JNK, and BMK1 signals (46). MK2 is one of the downstream kinases of p38 MAPK and is activated in the process of IBD (20). It is reported that MK2 regulated neutrophil activation by p38-dependent and ERK-dependent signal pathways (39,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Mourey et al (32) reported that MK2 contributed to intestinal inflammation in the progression of IBD. Wang et al reported that MK2 inhibitor could reverse DSS-induced acute colitis by inhibiting the production of a series pro-inflammatory cytokines in the colon and exerted anti-inflammatory effects against inflammatory disease (20,33,34). But the specific relationship between MK2 and IBD was not clear and needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations